2018
DOI: 10.2478/joeb-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Screening post-menopausal women for bone mineral level by bioelectrical impedance spectroscopy of dominant arm

Abstract: Dominant arm bioimpedance spectroscopy (BIS) and lumbar and hip dual energy X-ray absorptiometry (DXA) measurements were conducted simultaneously on 48 post-menopausal women, aged between 43 and 86 years, with no hip or arm fracture history at Department of Radiology of Istanbul University Cerrahpasa Hospital. According to lumbar DXA results, 21 women were classified as normal, 22 as osteopenia and 5 as osteoporosis; whereas hip DXA results classified 30 women as normal, 15 as osteopenia and 3 as osteoporosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This provided a new biomarker for BMD using BIVA [ 51 ]. Accordingly, previous studies have already demonstrated the existence of a correlation between BIA and BMD [ 53 , 54 ].…”
Section: Bia Application Under Physiological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provided a new biomarker for BMD using BIVA [ 51 ]. Accordingly, previous studies have already demonstrated the existence of a correlation between BIA and BMD [ 53 , 54 ].…”
Section: Bia Application Under Physiological Conditionsmentioning
confidence: 99%
“…In older adults is documented a decrease in bone mineral density (BMD) [ 51 ], the parameter for determining the severity of osteoporosis, which is defined as a low bone mass associated with the appearance of microarchitectural changes in the bone [ 52 ]. In addition to aging, postmenopausal osteoporosis also results in a change in mineral bone density due to a loss of trabecular bone as a result of changes in body composition and hormone levels [ 53 ].…”
Section: Bia Application Under Physiological Conditionsmentioning
confidence: 99%
“…Recent studies have indicated that bioelectrical impedance vector analysis (BIVA), its phase angle (PhA), the whole body, spine, and pr of middle-aged and elderly people. The BMD of the proximal femur has a certain correlation, especially in the lower PhA, which is related to osteoporosis [11][12][13] . Bioelectrical impedance analysis (BIA) is a noninvasive method for estimating the composition of the body according to the degree of resistance of the body tissue by passing a low-intensity current through the body.…”
Section: Introductionmentioning
confidence: 99%